2004
DOI: 10.1063/1.1682680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gate oxidation method on electrical properties of metal-oxide-semiconductor field-effect transistors fabricated on 4H-SiC C(0001̄) face

Abstract: Articles you may be interested inA methodology to identify and quantify mobility-reducing defects in 4H-silicon carbide power metal-oxidesemiconductor field-effect transistors Influence of the surface morphology on the channel mobility of lateral implanted 4H-SiC (0001) metal-oxidesemiconductor field-effect transistors J. Appl. Phys. 112, 084501 (2012); 10.1063/1.4759354 Effect of nitric oxide annealing on the interface trap density near the conduction bandedge of 4H-SiC at the oxide /(1120) 4H-SiC interface E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 18 publications
3
151
1
Order By: Relevance
“…3 However, it has been reported recently that high-quality epitaxial films have been successfully grown on the 4H-SiC C face and achieved ch of over 100 cm 2 / V s by pyrogenic oxidation technique, i.e., thermal oxidation in a mixture of oxygen and hydrogen ambient, followed by hydrogen annealing. [4][5][6][7][8] These reports have shown that the electrical characteristics of MOSFETs obtained by dry oxidation of the 4H-SiC C face are significantly poorer than those obtained by wet oxidation of the 4H-SiC C face. 7 In contrast, in the case of the 4H-SiC Si face, the difference in the electrical characteristics between wet and dry oxidations is not very significant.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…3 However, it has been reported recently that high-quality epitaxial films have been successfully grown on the 4H-SiC C face and achieved ch of over 100 cm 2 / V s by pyrogenic oxidation technique, i.e., thermal oxidation in a mixture of oxygen and hydrogen ambient, followed by hydrogen annealing. [4][5][6][7][8] These reports have shown that the electrical characteristics of MOSFETs obtained by dry oxidation of the 4H-SiC C face are significantly poorer than those obtained by wet oxidation of the 4H-SiC C face. 7 In contrast, in the case of the 4H-SiC Si face, the difference in the electrical characteristics between wet and dry oxidations is not very significant.…”
Section: Introductionmentioning
confidence: 96%
“…[4][5][6][7][8] These reports have shown that the electrical characteristics of MOSFETs obtained by dry oxidation of the 4H-SiC C face are significantly poorer than those obtained by wet oxidation of the 4H-SiC C face. 7 In contrast, in the case of the 4H-SiC Si face, the difference in the electrical characteristics between wet and dry oxidations is not very significant. [9][10][11] It is therefore very important to clarify the differences in the interface structures between the wet and dry oxides.…”
Section: Introductionmentioning
confidence: 96%
“…6(b)). 3,4,6,7,[10][11][12][13]16 The evaluated N T was in the range of 10 12 -10 13 cm −2 , which is extremely low when compared with the surface atomic density on SiC (more than 1 × 10 15 cm −2 ). Then, it has been found that very small part of the interface atoms form interface states.…”
Section: -7mentioning
confidence: 99%
“…However, the low channel currents at the SiO 2 /4H-SiC interfaces remain an important issue, despite extensive studies for more than a decade. [1][2][3][4][5][6][7][8][9][10] Although the interface states have been assumed to be a main cause of the low channel current, 2,3,6,7,10,16 a clear correlation between the interface state density (D IT ) and the channel performance has not been determined. 11 We recently showed that the peak n-channel field-effect mobility (µ FE,peak ) at room temperature is roughly inversely proportional to D IT for samples on the (0001), (000-1), and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) faces (the Si-, C-, and a-faces, respectively) after dry/nitridation and pyrogenic/hydrotreatment processes, 12 where D IT was evaluated by the C−ψ S method 13 at 0.2 eV below the conduction band edge (E C −E T = 0.2 eV) using MOS capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…28,29) The sample irradiated with the remote nitrogen plasma was transferred back to the load lock chamber and was exposed to the atmosphere. The atomic composition on the sample surface was analyzed by X-ray photoelectron spectroscopy (XPS) and high-resolution Rutherford back scattering (HRRBS).…”
Section: Methodsmentioning
confidence: 99%